Salvadori’s Duck of New Guinea - Kear, J (Wildfowl, 1975)
This paper reviews the biology of Salvadori’s Duck Salvadorina (Anas) waigiuensis, the only waterfowl species endemic to New Guinea. The bird appears to be physically adapted to living in mountain torrents, but is also found in other habitats. Pairs probably stay together year round and are highly territorial. Nesting occurs mainly from May to September; the eggs, at about 58 g, are very large in relation to the size of the female and the clutch of three eggs is small. It is suggested that the species shows affinities with the Torrent Duck Merganetta armata, and possibly the Blue Duck Hymenolaimus malacorhynchos, which are not merely the result of convergence. Further research is needed.